Analisa Hukum Tindak Pidana Gratifikasi Terhadap Hasil Audit Opini Wajar Tanpa Pengecualian (WTP) yang Dilaksanakan Badan Pemeriksa Keuangan (BPK) - Diana Novianti (Justici, 2019)
Efforts to safeguard the finances managed by the state, of course there is a need for special institutions that monitor them. Especially in Indonesia, the state institution is the Supreme Audit Board of the Republic of Indonesia (hereinafter abbreviated as BPK). In reality, the purpose of the audit conducted by the BPK in the process of its implementation, there are still found irregularities or crimes. One of the cases that is often associated with the BPK is the existence of gratuities aimed at manipulating the results of unqualified opinion (WTP) audits conducted against government agencies. The formulation of the problem of this research is how the legal process of gratification acts against BPK officials who make the results of WTP opinion audits in the perspective of criminal law and how to preventive measures in preventing acts of gratification against BPK officials who make WTP opinion audit results. The research method used is normative juridical research. The conclusion of this research is the act of gratification against BPK officials who made the results of the WTP opinion audit based on Article 5 paragraph 1 letter a, or Article 5 paragraph 1 letter b, or Article 13 of the Corruption Act and Article 64 KUHP juncto Article 55 paragraph 1 Criminal Code. The recipients of bribes are threatened with a maximum of 3 years imprisonment based on Article 12 letter a, or Article 12 letter b, or article 11 of the Corruption Act and Article 64 KUHP in conjunction with Article 55 paragraph 1 of the Criminal Code. Preventive efforts in preventing gratification of BPK officials who make WTP opinion audit results not only by raising the salaries of their employees but also by increasing the morality of these employees as well as a strict system of reward and punishment, in addition to the superiority of the superior to subordinates. .